Business Sustainability Analysis of On-Grid POME-Based Biogas Power Plant; A Resource-Based Theory Approach - Hari Yuwono, By; Setiawan, Margono; Fajri Ananda, Candra; ., Sudjatno (International Journal of Engineering and Technology, 2026)
The purpose of paper is to estimate the electricity generated from palm oil mill with fresh fruit bunch processing capacity of 45, 60 and 90 ton/h and analyse the business sustainability of grid connected POME-based biogas power plant using resource-based theory (RBT). The process of biogas formation and generation of electricity from palm oil mill effluent (POME) is described. Biogas is formed from anaerobic digestion of POME (organic materials). Biogas mainly consists of 50% to 75% methane (CH4). Methane (CH4) has larger impact to the global warming then CO2. Therefore, the use of methane-capture technology and conversion of CH4 into electricity will significantly reduce greenhouse gases (GHG) emissions to the environment. Various methods of anaerobic digestion on POME have been studied. However, commercial installations of anaerobic digestion normally use pond and tank systems due to performance and cost consideration. A mathematical method is used to calculate electricity generation potential from the palm oil mills (POMs) based on COD (chemical oxygen demand) of POME and the mill capacity in processing fresh fruit bunch (FFB) per hour. Business sustainability of biogas power plant from POME will depend on the level and durability benefit created from combination of resources against other alternatives. This paper also provides a model for validating sustainability of on-grid POME-based biogas power plant using resource-based theory (RBT). The validation using case studies from operational on-grid POME-based biogas power plant is a subject for future research.
Keywords: biogas; biogas from pome; electricity from biogas; business sustainability; alternative energy.